The impact of solar ultraviolet radiation on fish: Immunomodulation and photoprotective strategies. Issue 1 (6th November 2019) - Lawrence, Karl P.; Young, Antony R.; Diffey, Brian L.; Norval, Mary
Abstract: One of the many environmental factors affecting the health of both farmed and wild fish is exposure to solar ultraviolet radiation (UVR). These rays penetrate to biologically relevant depths in natural waters and cause changes ranging from embryo malfunction to the production of heat‐shock proteins. As suppression of cell‐mediated immunity has been shown to follow irradiation of mammals, the possibility of UVR‐induced modulation in immune responses in fish is considered in this review. It is suggested that, after adsorption of UV photons by surface chromophores, dendritic‐like cells may be activated by immune mediators, leading to the generation of T‐ and B‐cell subsets with down‐regulatory activity. A limited number of studies involving infection of irradiated fish with bacteria, nematodes and protozoa have demonstrated an increased microbial load and lack of clearance, with associated changes in a variety of immune parameters. These preliminary results indicate that exposure of fish to solar UVR leads to less effective control of infections. Strategies evolved by fish to avoid overexposure to UVR include photoenzymatic repair, nucleotide excision repair, pigments, mycosporine‐like amino acids and habitat selection. The welfare of farmed fish is of concern currently. The detrimental effects of excessive sun exposure on the health of fish require recognition, and procedures put in place to minimize such consequences.